Willingness to Pay for a Maternity Waiting Home Stay in Zambia. (2nd November 2016) - Vian, Taryn; White, Emily E.; Biemba, Godfrey; Mataka, Kaluba; Scott, Nancy
Abstract : Introduction: Complications of pregnancy and childbirth can pose serious risks to the health of women, especially in resource‐poor settings. Zambia has been implementing a program to improve access to emergency obstetric and neonatal care, including expansion of maternity waiting homes‐residential facilities located near a qualified medical facility where a pregnant woman can wait to give birth. Yet it is unclear how much support communities and women would be willing to provide to help fund the homes and increase sustainability. Methods: We conducted a mixed‐methods study to estimate willingness to pay for maternity waiting home services based on a survey of 167 women, men, and community elders. We also collected qualitative data from 16 focus group discussions to help interpret our findings in context. Results: The maximum willingness to pay was 5.0 Zambian kwacha or $0.92 US dollars per night of stay. Focus group discussions showed that willingness to pay is dependent on higher quality of services such as food service and suggested that the pricing policy (by stay or by night) could influence affordability and use. Discussion: While Zambians seem to value and be willing to contribute a modest amount for maternity waiting home services, planners must still address potential barriers that may prevent women from staying at the shelters. These include cash availability and affordability for the poorest households.